THE ANALYSIS OF HUMAN RESOURCES MANAGEMENT (HRM) IN MARITIME AFFAIRS - Goran Vučur; Ivica Miloslavić; Maro Bošnjak (Ekonomski Vjesnik, 2016)
Specifics of human resources management in maritime affairs is reflected in the fact that part of the staff of enterprises is displaced on ships which represent a specific and isolated environment. Specifics of human resources management on ships are focused to decision-making in crisis situations, the deployment of personnel and work load, and giving orders to perform certain tasks. In this context it is necessary to examine the management of human resources which should include managing, motivation, rewarding, communication, education, advancement, decision-making and employee satisfaction in the specific environment. The aim of the research is to analyze the above stated parameters and connect them with the characteristics of companies in the sector of maritime logistics. The purpose of this paper is to provide an insight into the human resources management in companies involved in logistics in maritime transport i.e. delivery and transport of goods. Taking into account their differences, it can be concluded that companies in the maritime industry have different human resource management systems, which affects the company's business. The research methodology is based on the collection of data through questionnaires and databases created from them. The study included a total of 31 companies. According to the collected data, statistical analysis will be conducted which will be based on correlation and descriptive statistics. The analysis of the theoretical basis has not confirmed the existence of similar studies that take into account the observation of human resources management on ships. Therefore, it can be concluded that the research will be of interest for the field of business logistics as well as the whole scientific and professional community. Recommendations related to the current and future human resource management in maritime companies will be given in the conclusion.